BIOTRANSFORMATION OF CINCHONA ALKALOID COMPOUNDS BY MOLD Xylaria sp.TO CINCHONA N-OXIDE ALKALOIDS [Studies on Endophytic Microbes of Cinchona spp. plants (5)] - Partomuan Simanjuntak; Bustanussalam .; Titik K. Prana; K. Ohashi; Hirotaka Shibuya (Indonesian Journal of Pharmacy, 2002)
A biotransformation study on alkaloid chinchona compounds (quinine, quinidine, cinchonidine, cinhonine) by endophytic microbe from Cinchona succirubra have been done. The biotransformation for 2 days after preculture yielded cinchona N-oxide compounds (quinine N-oxide, quinidine N-oxide, cinchonidine N-oxide, cinchonine N-oxide) alkaloids and the bioassay of the compounds also showed effectiveness as antimalaria. Purification the biotransfomed compound was conducted by a high performance liquid chromatograph (HPLC) and determination of chemical structure was done based on carbon nuclear magnetic resonance (NMR).Key words : Biotransformation, endophyte microbe, Xylaria sp., Cinchona succirubra Pav., cinchona alkaloid, quinine, quinine N-oxide